Забезпечення надійності експлуатації технологічної системи важких верстатів - Клименко, Г.; Квашнін, В. (Національний технічний університет "Харківський політехнічний інститут", 2019)
В роботі вирішена задача підвищення надійності експлуатації технологічної системи важких верстатів шляхом визначення раціональної стратегії її обслуговування, Представлена система показників надійності процесу експлуатації технологічної системи важкого токарного верстату, яка складається з верстату, деталі, інструменту і верстатника. Показником надійності системи запропоновано використовувати коефіцієнт готовності, який включає характеристики як інтенсивності відмов системи, так і інтенсивність відновлення її працездатності. Статичний аналіз роботи системи дозволив виявити структуру часу її технологічної роботи, щільність розподілу часу простоїв системи, пов’язаних з обслуговуванням інструменту. Розроблено математичні моделі коефіцієнта готовності для двох стратегій експлуатації технологічної системи важкого токарного верстата: незалежного обслуговування системи верстатниками і спільного обслуговування кількома верстатниками. Застосування розроблених математичних моделей дозволяє підібрати необхідну стратегію обслуговування системи для забезпечення певного рівня надійності її експлуатації.

The paper solves the problem of increasing the reliability of operation of the technological system of heavy machines by determining a rational strategy for its maintenance. The analysis of the literature showed that there are various indices of reliability, durability, maintainability, which partially characterize reliability, to assess the reliability of the technological system. To determine them, you must have a large number of statistical studies. But there is a need to develop universal mathematical dependencies to predict a specific maintenance strategy for the technical system of heavy machines. Research methods include static data collection of heavy machine tools, the reliability of which is determined mainly by machine downtime associated with the failure of cutting tools, which are the weakest element of the technological system. Mathematical processing of statistics results allows to determine the density distribution of system failures, as well as the intensity of failures and system recovery. A feature of the recovery of heavy machines is the location of their caliper on a high platform, which makes it difficult to replace the tool, whose weight reaches 25 kg. The paper presents a system of indicators of the reliability of the process of operation of the technological system of a heavy lathe, which consists of machine parts, tools and machine operator. Statistical analysis of the system allowed to identify the structure of the time of its technological work, the density of distribution of the system downtime associated with the maintenance of the tool. The maintenance of the technological system of a heavy machine is carried out by 2 machine operators (the main and the assistant). The paper considers two strategies of machine maintenance - independent and common. The criterion for choosing a rational strategy is the level of reliability of the system. A universal indicator of the reliability of the technological system is proposed to use the system availability ratio. It is assumed that the system can be in one of three possible states at a certain point in time: the system health state, the state when only one tool is operational, the state in which all tools are restored. The system availability function is the probability of being in a working system state. Using the Markov approach to assessing the reliability of the system, a matrix of transitions from one state of the system to another is written, which allows us to obtain algebraic equations, solving which we obtain mathematical models for determining the availability factor for various maintenance strategies of the technological system. Mathematical models of availability factor have been developed for two strategies for operating a heavy lathe technological system: independent maintenance of the system by machine operators and general maintenance by several machine operators. With the joint maintenance of a technological system by two machine operators, the level of reliability of the system is significantly increased compared with independent maintenance. For the general case with a certain number of cutting tools and a certain amount of machine operators, a mathematical expression was obtained for calculating the availability factor, which determines the probability of a healthy state of the system. The use of the developed mathematicalmodels makes it possible to select the necessary system maintenance strategy to ensure a certain level of reliability of its operation. The developed mathematical models are used for statistical modeling of the maintenance of the technological system of a heavy lathe, whose downtime has a greater cost. Knowing the failure rate and system recovery, you can choose the necessary service strategy to obtain a desired level of reliability. Possible solution of the inverse problem for a given system availability in various combinations of λ and μ, which characterize the intensity of failures and recovery of the tool, which are implemented at the stage of tool selection. Since most often in production conditions heavy lathes are serviced by two machine operators, in this case the most effective from the point of view of reliability is the joint maintenance of the technical system.
Reliability assurance technological systems exploitation of heavy lathe
Keywords: різальний інструмент; exploitation of heavy lathe